МЕТОДИЧНИЙ ІНСТРУМЕНТАРІЙ ВІДБОРУ ТА МАСШТАБУВАННЯ СТАРТАПІВ - Liubov, Vodianka; Стахова, Наталія Петрівна; Грунтковський, Володимир (My University, 2024)
The research substantiates the need to provide specific practical and methodical tools for the management of startups. A modification of the SWOT analysis methodology with additional groups of factors and their combinations is proposed. Developed test matrix and scale matrix of SWOT analysis for assessment of viability and strategic planning of startup scaling. A startup rider (material) is proposed for evaluating startups, which may include the following steps. Step 1. The main goals, tasks of the startup, as well as motives for all participants in the consumption of the product are formed and written out. Step 2. All categories of factors are entered into the table. Step 3. All factors are combined to build a strategic line of startup implementation. Step 4. Conclusions are summarized taking into account the received data. Business scaling is possible along vertical and horizontal lines. Horizontal scaling is an increase in profit due to the opening of new outlets or a coverage area (offline business), vertical scaling is a transition to a qualitatively new level and an increase in profit due to changes in the assortment, quality of the product, its cost and service. It is desirable to develop these lines one after the other in order to effectively concentrate resources. Formed formalization of factors for automated data processing. Thus, SWOT analysis can, from the point of view of methodological support, act as a comprehensive practice oriented tool for deciding on scaling strategies, and also, as we have seen, with a specific modification, it helps to calculate the degree of viability of a startup under existing and forecasted conditions and to determine strategic lines, compare and select promising startups. We believe that it is appropriate to use the Scaling up technique, in which scaling focuses on four main areas of decision making: people, strategy, execution and funds. The results of these studies (internal factors) can be used further to build the scale matrix of the SWOT analysis The results of the analysis of the test and scale matrix of the SWOT analysis of the startup can be used to draw up a business plan and present it to investors, as well as to interested partners at the pre investment stage, to search for possible methods of its promotion, in the process of improving the introduced product at the scaling stage
METHODICAL TOOLKIT FOR THE SELECTION AND SCALING OF STARTUPS
Keywords: стартап; тест-матриця; SWOT-аналіз; інновації; масштабування стартапу